ANALISIS STRUKTUR DAN POLA PERTUMBUHAN IKAN PAYANGKA (Ophieleotris aporos) DI DANAU LIMBOTO - Mokoginta, Ayatola R.; Mamangkey, Jefry J.; Rampengan, Mercy M. F; Ogi, Nova L I M; Lawalata, Helen J. (SOSCIED, 2024)
Payangka fish (Ophieleotris aporos) is a fish that lives in freshwater and has the ability to survive in the midst of competition with other fishes that are very tough. This study aims to analyze the structure of payangka fish and the growth pattern of payangka fish in Lake Limboto. Fish samples were caught using a 2 cm net with a net length of 7 m and then a 1 m serok (sibusibu) with a total sample of 1003 fish. The results of the length structure analysis of payangka fish obtained a length range of 9.15 - 19.05cm with an average of 12.45 cm and the results of the weight structure analysis obtained a range of 9.27 - 47.97 grams with an average of 13.57 grams. The results of the analysis of the relationship between length and weight of payangka fish obtained allometric growth pattern (b = 2.92), b < 3 which means that weight gain is faster than length gain..